Kinematic analysis of a 3-DOF asymmetrical planar parallel robot mechanism - Metin Toz (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, kinematic analysis of a planarparallel robot mechanism with three degrees of freedom (DOF) was performed. Thedifference of the selected mechanism from the other planar mechanisms is thatit has an asymmetric leg structure. In order to provide the asymmetry, a leg of3-RPR (R: Revolute joint, P: Active prismatic joint) symmetricalplanar robot mechanism was replaced by a RRR (R: Active revolute joint)type leg and the asymmetrical planar parallel robot named RPR2RRR1mechanism has been obtained. Inverse kinematics, Jacobian matrix andsingularity free workspace analysis were performed for the proposed mechanism.In addition, the performance of this mechanism is compared with the 3-RPRmechanism, which is a symmetric planar parallel robot mechanism. According tothe obtained results, it has been shown that the workspace of the proposedmechanism is better than the 3-RPR mechanism in terms of both the numberof points that can be reached by the end-effector and the limit values of theorientation angle.